The Effects of Facebook on Automobile Purchasing Behavior among International Students in Northern Cyprus - Nwankpa, Raphael Ebuka (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Purchasing an automobile is one of the most expensive decisions among younger generations, yet an increasing number of international university students in Northern Cyprus keep acquiring luxury ones. Even so, it is unclear what motivates international students into such expensive purchasing behavior, and as a result this study seeks to investigate factors that prompt such behavior, and the effects of Facebook as a new media tool on automobile purchasing behavior among international students in Northern Cyprus. It aims to establish a relationship between Facebook use, brand loyalty, automobile purchasing behavior, and other moderating factors such as need to boost self-esteem and travel convenience, as well as age and family income. This is a quantitative research design. It uses online questionnaires, with 400 (133 female, 267 male) randomly selected international students in Northern Cyprus, from the 2020/2021 spring semester as study participants. With Google forms, 40-question English questionnaires were created and distributed online through Whatsapp, Facebook, and Snapchat. The study found several links between Facebook and automobile purchasing behavior among international students. For example, it found links between brand loyalty and Facebook use, automobile reviews and automobile purchasing behavior, and self-esteem/convenience and automobile purchasing behavior. However, no relationship was found between automobile purchasing behavior and the ages/yearly family income of international students in Northern Cyprus. Consequently, the findings showed a relationship between Facebook and automobile buying behavior among international students in Northern Cyprus.

ÖZ: Otomobil satın almak genç nesiller arasında en pahalı kararlardan biri olmasına rağmen, Kuzey Kıbrıs'ta giderek artan sayıda uluslararası üniversite öğrencisi lüks araba satın alma eğilimi göstermektedir. Ancak üniversite öğrencilerinin bu denli pahalı satınalma davranışına iten dürtü ise pek net değildir. Bu bağlamda, bu çalışma, Kuzey Kıbrıs'taki uluslararası öğrenciler arasında otomobil satın alma davranışını, yeni medya aracı olarak Facebook kullanımı ve otomobil satın alma davranışı üzerindeki etkilerini araştırmaktadır.Bu çalışmanın amacı, üniversite öğrencilerinin Facebook kullanımı, marka sadakati, otomobil satın alma davranışı ve benlik saygısını artırma ihtiyacı ve seyahat kolaylığı gibi diğer faktörler ile yaş ve aile geliri arasında bir ilişkiyi araştırmaktır. Bu çalışma, nicel araştırma tasarımı kullanılarak çevrimiçi anket kullanılmasına dayanmaktadır. Evren örneklemi olarak Kuzey Kıbrıs'ta 2020/2021 bahar döneminden rastgele seçilen 400 (133 kadın, 267 erkek) uluslararası öğrenci kullanılmıştır. Google ile 40 soruluk İngilizce anketler hazırlanmış ve whatsapp, Facebook ve Snapchat aracılığıyla öğrencilere iletilmiştir. Bu çalışma sonuncunda, Kuzey Kıbrıs'taki uluslararası öğrencilerin Facebook kullanımı ile marka sadakati, otomobil değerlendirmeleri ve otomobil satın alma davranışı ve benlik saygısı/kolaylık ve otomobil satın alma davranışı arasında istatistik ilişkiler bulunurken, otomobil satın alma davranışı ile yaş/yıllık aile geliri arasında bir ilişki bulunmamaktadır. Netice itibarıyla Sonuçlar Facebook ile otomobil satın alma davranışı arasında Kuzey Kıbrıs’taki uluslarası öğrenciler arasında bir ilintiye işaret etmektedir.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2021. Supervisor: Asst. Prof. Dr. Umut Ayman.
Keywords: Communication and Media Studies Department; Consumer behavior--Marketing Management; Customer Relations; Consumer Preferences; Facebook, purchasing behavior, consumer behavior, automobile, social networking sites, new media, brand, brand loyalty